PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN DENGAN GENDER SEBAGAI VARIABEL MODERASI PADA KONSUMEN MIE GACOAN DI BANDAR LAMPUNG - Deandra Putri Zahra; MS, Mahrinasari (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to determine the effect of service quality on customer satisfaction of Mie Gacoan in Bandar Lampung; determine the effect of product quality on customer satisfaction of Mie Gacoan in Bandar Lampung; analyze gender as a moderating variable group influencing the relationship between service quality and customer satisfaction of Mie Gacoan in Bandar Lampung; and analyze gender as a moderating variable group influencing the relationship between product quality and customer satisfaction of Mie Gacoan in Bandar Lampung. The service quality variable has a positive and significant effect on customer satisfaction of Mie Gacoan in Bandar Lampung. The highest rating was found on the indicator